Risk factors associated with bacterial bacteria in a hemodialysis unit (Jóvenes en la Ciencia, 2024)
In Mexico, the Hospital Network for Epidemiological Surveillance (RHOVE) reported an incidence of Bacteremia Related to Endovascular Catheter (BRC) of 7.4 deaths per 100 thousand inhabitants. The use of tunneled Central Venous Catheters (CVC) increases the risk of bacteremia 7 and 20 times, respectively, compared to arteriovenous fistulas. In 2017, a prevalence of Chronic Kidney Disease (CKD) of 12.4 deaths per 100 thousand inhabitants in Mexico was reported. OBJECTIVE: Determine the risk factors associated with bacteremia in a second level hemodialysis unit. A quantitative, descriptive, cross-sectional and retrospective study was conducted. The study population was patients undergoing hemodialysis in a secondary care unit. To collect the information, an instrument was used which consisted of two sections, sociodemographic and clinical data of the patients and risk factors associated with bacteremia. Cronbach's alpha was used for the reliability of the instrument. Descriptive statistics were considered for the sociodemographic variables and to determine the risk association between the factors and bacteremia, the Odds Ratio (OR) was applied. 74 patient records from the Hemodialysis (HD) service were censused. To evaluate the strength of association between the variables, risk factors and bacteremia, the Odds Ratio (OR) with a 95% Confidence Interval (CI) was calculated. It was shown that 11 factors were considered risk to be related to the appearance of bacteremia, such as; alcohol consumption 1.0(.9-1.0), systolic arterial hypertension (SAH) 5.8(.6-49.6), diabetes mellitus (DM) 3.9(.8-18.4), low serum albumin levels 2.6(.2-24.5) , number of puncture attempts 11.0(.8-138.9), CVC manufacturing material-permacath catheter 1.1(1.0 - 1.2), mahurkar catheter 3.9(.7-19.3), electrolyte imbalance 3.1(.6-14.6), disease bone 1.1(1.0-1.2), nephroangiosclerosis 2.0(.2-18.8), diabetic nephropathy 1.2(1.1-1.3). However, their confidence intervals were not significant, contrary to two of the variables studied that were found to be protective factors for bacteremia. Adequate asepsis technique (OR= .01 CI: .016-.445) and care of the insertion point (OR= .0 CI: .0-.3). The prevalence of BCR associated with risk factors in a hemodialysis unit was 6.75%. The bacteremias found in the files were; Klebsiella pneumanoie 16.7%, Enterococcus 16.7% and Enterobacter 16.7%. These results suggest that, due to the low rate of bacteremia found in the Hemodialysis Unit, it was determined that the nursing staff has adequate asepsis techniques, thus preventing the spread of infections.Key words: Risk Factors, Bacteremia, Hemodialysis.